ARTHROCENTESIS FOR TEMPOROMANDIBULAR JOINT PAIN DYSFUNCTION SYNDROME - Jamot, Shahid Rauf; Khan, Zafar Ali; Khan, Tahir Ullah; Warraich, Riaz Ahmad; Farooq, Muhammad (Journal of Ayub Medical College Abbottabad, 2017)
Background: Temporomandibular joint (TMJ) dysfunction is painful condition of facial musculoskeletal system. Arthrocentesis is less invasive treatment of TMJ dysfunctions. It has been used to treat variety of TMJ disorders. The objective of this study was to determine the success of arthrocentesis in TMJPDS patients where conservative treatment had failed. Methods: This descriptive case study of 45 patients was completed in 6 months at Outpatient Department of Oral and Maxillofacial Surgery, Mayo hospital Lahore. TMJPDS Patients who were unresponsive to conservative treatment were included in this study. The study consisted of a single arthrocentesis procedure performed by a single oral surgeon per patient. Visual Analogue Scale was used to record pain while maximum mouth opening was measured by the interincisal distance in millimetres, at 1 month and 2 months after the treatment. Success was measured two months after arthrocentesis. Results: 30 (66.7%) patients had no pain and 15 (33.3%) patients had mild pain. Similarly, 16 (35.5%) patients had maximum mouth opening more than 30mm and 29 (64.5%) patients had less than 30mm mouth opening, two months after arthrocentesis procedure. Conclusion: Arthrocentesis is very effective in patients suffering from TMPDS by reducing pain and discomfort and increase in mouth opening. This procedure should be considered in TMPDS patients who do not respond to conservative treatment. Keywords: Temporomandibular joint; Arthrocentesis; TMJPDS